2016
DOI: 10.1016/j.biortech.2016.07.103
|View full text |Cite
|
Sign up to set email alerts
|

Removal of volatile fatty acids and ammonia recovery from unstable anaerobic digesters with a microbial electrolysis cell

Abstract: Continuous assays with a microbial electrolysis cell (MEC) fed with digested pig slurry were performed to evaluate its stability and robustness to malfunction periods of an anaerobic digestion (AD) reactor and its feasibility as a strategy to recover ammonia. When performing punctual pulses of volatile fatty acids (VFA) in the anode compartment of the MEC, simulating a malfunction of the AD process, an increase in the current density was produced (up to 14 times, reaching values of 3500mAm(-2)) as a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…The pH of the bulk solution in the anode compartment remained in the range 7.3–8.8, thus being appropriate for microbial activity (Figure (b)). In a previous work using a MEC, current density increased in response to each VFA pulse . This behaviour agrees with the low coulombic efficiencies achieved when working with MFCs (1–4%) compared with those achieved in MEC mode (11–18%) .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The pH of the bulk solution in the anode compartment remained in the range 7.3–8.8, thus being appropriate for microbial activity (Figure (b)). In a previous work using a MEC, current density increased in response to each VFA pulse . This behaviour agrees with the low coulombic efficiencies achieved when working with MFCs (1–4%) compared with those achieved in MEC mode (11–18%) .…”
Section: Resultssupporting
confidence: 88%
“…However, MFC performance against AD destabilisation has not been studied in depth, nor has its influence on ammonia recovery. A previous study performed under microbial electrolysis cell (MEC) mode, thus applying a low amount of energy to the system to boost the process, has shown that VFA accumulation in pig slurry digestates can be removed in a MEC reactor while recovering ammonium at the same time . That study also showed that higher MEC performances were attained when the AD was in an unstable or inhibited state.…”
Section: Introductionmentioning
confidence: 98%
“…Owing to the slow growth and high sensitivity of methanogens to various inhibitory compounds, the organic acids (acetic and propionic acids) produced through fermentation easily accumulate under a high organic load during the anaerobic digestion (Franke‐Whittle, Walter, Ebner, & Insam, 2014). In contrast, in polarized systems, organic matter can be rapidly depleted by exoelectrogens using an anode as an electron acceptor (Asensio, Fernandez‐Marchante, Lobato, Caňizares, & Rodrigo, 2016; Cerrillo, Viñas, & Bonmati, 2016). This is consistent with the higher removals of acetic acid and propionic acid in the polarized system than in the open‐circuit system investigated in this study (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Integration of AD with BES can enrich exoelectrogens (anode) and hydrogenotrophic methanogens (cathode) . The degradation rate of recalcitrant compounds in wastewater is higher in the integrated MEC‐AD system, and the effluent has been found to have low organics and ammonium contents . Dou et al .…”
Section: Research Advancesmentioning
confidence: 99%
“…163 The degradation rate of recalcitrant compounds in wastewater is higher in the integrated MEC-AD system, 76 and the effluent has been found to have low organics and ammonium contents. 122 Dou et al 163 reported that an MEC-AD had higher resilience to shock organic loading, and a potential of 2 V resulted in water electrolysis and led to a higher CH 4 production rate (105 mL L −1 day −1 ) and biogas CH 4 content (88.5 + 1.4%).…”
Section: Coupling Mec With Other Technologies For Value-added Applicamentioning
confidence: 99%